Impact of environmental taxation policies on civil aviation - a techno-economic environmental risk assessment - Nalianda Karumbaiah, D. (Cranfield University, 2012)
Sustainability of the aviation industry, as any other industry, depends on the elasticity of demand for the product and profitability through minimising operating costs and hence assessing and understanding the interdependency and effects of environmentally optimised solutions and emission mitigation policies, is paramount. The contribution to knowledge, from this research, is the development and application of assessment methodologies to better understand the effects that future potential environmental taxation may have on the adaptation of optimised “greener” operations and novel technologies. These studies are undertaken using a Techno-economic Environmental Risk Assessment approach (TERA). The first methodology introduced to assess optimised operation methods (based on operating cost analysis), demonstrated that carbon taxation has limited effect if applied in isolation. Increasing it to extreme levels, apart from resulting in an increase in operational costs and raising governmental revenues, may not necessarily result in influencing an airline operator’s operational strategy to move to greener solutions. Instead, an application of a taxation level, commensurate to global standards, coupled with an improved air traffic management system, would allow aircraft to fly closer to their design efficiency and hence aid in reducing the environmental impact. The second methodology introduced (based on an operating and investment cost analysis) allows the assessment of the economic viability of a new technology in comparison to a conventional technology, when considered in terms of relative increase in acquisition price and maintenance costs, for various emission taxation and fuel price scenarios. A study undertaken as a ‘proof of concept’, comparing a Counter Rotating Open Rotor (CROR) aircraft with a conventional aircraft, indicates that at a current fuel price and no carbon taxation, despite being demonstrated as a highly fuel efficient technology, a relative increase in acquisition price and maintenance costs in comparison to the conventional aircraft, could render the CROR technology, economically unviable. The work further demonstrates that for the CROR technology to be economically beneficial, a simultaneous introduction of emission taxes may be required. The study shows that in order to achieve lower environmental impact, the implementation of taxation with the introduction of greener technologies will evidently increase the cost of civil aviation operation. This research subsequently identifies the following questions, more of a ‘political and socio-economic nature’, to consider as part of further work.  If taxes above the global industry standards are introduced for the aviation industry, and they are higher in comparison to those applied on some other carbon intensive sectors, will it raise questions on equity of treatment?  If taxation is introduced, airline operators and the ticket price paying passengers being amongst the key stakeholders in the aviation industry, will such high pricing as demonstrated be practical for long term sustenance?  Will policies be driven by the fact that they will be aimed as a trade-off between achieving global sustenance of the industry and achieving environmental gain?  Will high taxation as demonstrated, have global acceptance or will it have to be compromised, based on the growth potential or GDP of a country/ region?